Practicality Pocketbook “Keanekaragaman Lepidoptera Di Hutan Mangrof” - Fadil Ramadhan; Mochamad Arief Soendjoto; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
Students are expecting to receive contextual material to make it easier for them to understand what they have learned. The solution to support this method is a teacher must make the teaching material with local wisdom. Booklet